2016
DOI: 10.7554/elife.13065
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization shapes the turnover of a bacterial transcriptome

Abstract: Spatial organization of the transcriptome has emerged as a powerful means for regulating the post-transcriptional fate of RNA in eukaryotes; however, whether prokaryotes use RNA spatial organization as a mechanism for post-transcriptional regulation remains unclear. Here we used super-resolution microscopy to image the E. coli transcriptome and observed a genome-wide spatial organization of RNA: mRNAs encoding inner-membrane proteins are enriched at the membrane, whereas mRNAs encoding outer-membrane, cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
239
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(266 citation statements)
references
References 65 publications
(105 reference statements)
15
239
1
Order By: Relevance
“…It has been shown to be membraneassociated in E. coli and B. subtilis, [3][4][5][6] but deployed throughout the nucleoid in Caulobacter. 10 Previous studies of ribosome localization in E. coli 24,25 and B. subtilis 12 revealed enrichment at the cell poles, where they are excluded from the nucleoid, while similar studies in Caulobacter revealed no apparent separation of ribosomes and the nucleoid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown to be membraneassociated in E. coli and B. subtilis, [3][4][5][6] but deployed throughout the nucleoid in Caulobacter. 10 Previous studies of ribosome localization in E. coli 24,25 and B. subtilis 12 revealed enrichment at the cell poles, where they are excluded from the nucleoid, while similar studies in Caulobacter revealed no apparent separation of ribosomes and the nucleoid.…”
Section: Discussionmentioning
confidence: 99%
“…10 In sharp contrast to RNase E sequestration to the inner membrane in E. coli, 4,5 RNase E in Caulobacter was observed to cluster along the central axis of the cell and nucleoid ( Fig. 3a- clustering metric from the integral between the two curves ( Fig.…”
Section: Rnase Ementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, FISH analysis revealed distinct, uneven patterns of localization and specific foci at one or both poles for the dinitrogenase reductase-encoding nifH transcripts of Klebsiella oxytoca and Azotobacter vinelandii with specific foci at one or both poles in K. oxytoca (69) . One intriguing hypothesis is that mRNAs can be targeted to the subcellular domains where their encoded protein products are required (cytoplasm, poles or inner-membrane) (65, 70, 71). For example, while the cat mRNA, encoding the cytoplasmic chloramphenicol acetyltransferase, was observed in a helix-like pattern in the cytoplasm of E. coli , the mRNA of lacY , encoding the membrane-bound lactose permease, was preferentially detected near the cytoplasmic membrane (65).…”
Section: Localization Of Messenger Rnasmentioning
confidence: 99%
“…While most studies have mainly looked at localization of only a single or small set of mRNAs, recently Zhuang and co-workers investigated the spatial organization of mRNAs in E. coli on the transcriptome scale (70). They designed complex FISH probe sets to visualize defined sets of mRNAs, categorized by the subcellular localizations of their encoded proteins, allowing examination of about 27% of all E. coli mRNAs.…”
Section: Localization Of Messenger Rnasmentioning
confidence: 99%